Same-Sex Marriage in Islamic Theology: Challenges, Responses, and Sharia Implications in Muslim Societies - Ismail Koto; Rahman Malik; Achmad Syarifudin (Pharos Journal of Theology)
This study aims to analyse the Islamic theological response to the phenomenon of same-sex marriage, focusing on the challenges, responses, and Sharia implications within Muslim societies. The urgency of this research emerges due to the increasing recognition and legalisation of same-sex marriages in various countries, posing a dilemma for Muslims in reconciling religious beliefs with changing social realities. The method employed is text-based qualitative analysis, examining verses from the Quran, Hadiths, and contemporary literature to explore theological interpretations of this issue. The findings indicate that the majority of Islamic theological views reject same-sex marriage, referencing traditional narratives that interpret homosexual relations as acts contrary to Sharia law. Further discussion highlights how Muslim societies around the world respond differently, ranging from stark rejection to efforts at more inclusive adaptation and dialogue. Recommendations include the need for in depth religious education and interfaith dialogue to enhance understanding and tolerance of this issue within the Sharia framework, as well as the development of policies that respect Islamic principles while considering global human rights.